Participation of Muslim Children in Elementary Education: Present Status, Government Policies and Role of Community. - Zaidi, S.M.I.A (2008)
India has not been able to achieve the goal of Universalisation of Elementary Education (UEE) till date and the problem in this regard seems to be the participation of children from educationally backward sections of population. It is perceived that even the participation of Muslim children in elementary education is far from satisfactory. This paper attempts to show the participation of Muslim children in elementary education and compares the performance of Muslims in this context with the Scheduled Castes, Scheduled Tribes and Other Backward Castes (OBCs). It critically examines the policies adopted and programmes implemented by the government for the educational development of Muslims in the country during the last few decades. The paper also highlights the role and the responsibility of the Muslim community in enhancing the participation of their children in education in general and in the elementary education in particular